Agar Extraction, Physical Properties, FTIR Analysis and Biochemical Composition of Three Edible Species of Red Seaweeds Gracilaria corticata (J. Agardh), Gracilaria dentata (J. Agardh) and Gracilariopsis longissima (S. G. Gmelin)........: Biochemical Composition of Three Edible Species - Qari, Rashida; Haider, Saima (Biological Sciences - PJSIR, 2021)
Three species of red algae Gracilaria corticata (J. Agardh), Gracilaria dentata (J. Agardh) and Gracilariopsis longissima (S.G. Gmelin), Steentoft, L. M; Irvine and Farnham (formerly Gracilaria verrucosa (Hudson) were collected from four different sites (Buleji, Hawks Bay, Manora and Paradise Point) of Karachi coast. The G. corticata was the dominant species and the highest yield of agar was compared to other studied species. The physical properties such as gel temperature, melting temperature, density, viscosity and gel strength showed large variations. Interestingly, the gel temperature, melting temperature, density, and gel strength had the highest value in G. corticata samples collected, while gel viscosity recorded the highest value in G. dentata samples. Intensive spectroscopic FTIR analysis was determined in all three species of G. corticata, G. dentata and G. longissima. The bands at 414.7/cm to 3917.2/cm represents stretching and bending vibrations of alcohol O-H, amine N-H, alkane C-H, alkyne C=C, nitriles C=N, carboxyl C=O, nitro aromatic N=O, alkane C-C, nitro methane C-N, aliphatic amines C-N, sulfoxides S=O, alkene C-H alkyl halide C-Cl, C-I groups. The ash content of all studied species (G. corticata, G. dentata and G. longissima) was in the range of 20-30%, while the carbohydrate content was in the range of 22-24%. The results of this study suggested the utilization of our natural resources present in Karachi coast. This could be achieved by determining the quantity and quality of agar in the edible species of Gracilaria/Gracilariopsis.